Prognostic value of VEGF-A expression and mutations in oral squamous cell carcinoma - Benish Aleem; Asif Ali; Wafa Naeem; Fouzia Nawab; Muslim Khan; Taj Ali Khan; Samrina Mohammad; Ihtisham Ul Haq; Haseena Nawaz; Muhammad Imtiaz; Ali Khurram (Arab Journal of Basic and Applied Sciences)
Oral squamous cell carcinoma (OSCC) is ranked among the most prevalent malignancies globally, particularly in South Asia. It has a poor survival rate due to late diagnosis and limited treatment options. Angiogenesis, driven by vascular endothelial growth factor-A (VEGF-A), is pivotal in progression of OSCC by promoting tumor growth and metastasis. A total of 27 OSCC tissue samples were subjected to whole exome sequencing (WES) to identify VEGF-A mutations, and immunohistochemistry (IHC) was performed on 50 OSCC samples to quantify VEGF-A expression levels. Mutations were screened against databases such as COSMIC and dbSNP, while PolyPhen-2, SIFT, and MutationTaster were used to predict their pathogenicity. Kaplan–Meier analysis evaluated the relationship between VEGF-A mutations, histoscores, and overall survival (OS). Eleven mutations were identified in the VEGF-A gene, with 7.4% (2/27) being non-synonymous and 33% (9/27) synonymous. One non-synonymous mutation (p.E104K) was novel and previously undocumented. SIFT and MutationTaster predicted these non-synonymous mutations as pathogenic, while PolyPhen-2 classified them as benign. IHC analysis showed varying VEGF-A expression levels, with half of the cases exhibiting high histoscores. Patients with lower VEGF-A expression demonstrated improved survival, with a mean survival advantage of approximately 6 months over those with high VEGF-A levels. However, no significant correlation was found between VEGF-A mutations and OS (p = 0.38). This study highlights the complex role of VEGF-A mutations in OSCC. While non-synonymous mutations destabilized VEGF-A, the lack of correlation between mutations and OS suggests additional mechanisms influencing tumor progression. Reduced VEGF-A expression confers a survival benefit, reinforcing the potential of VEGF-A as a prognostic marker and therapeutic target. These findings underscore the importance of integrating genetic and proteomic profiling for personalized treatment strategies in OSCC.